Auditoria social dos 'negócios migratórios' das ações de assistência emergencial e humanitária em Roraima - Albuquerque, Janison Machado de (2022)
This Master's Thesis defended in the Postgraduate Program in Society and Borders (PPGSOF) of the Federal University of Roraima developed studies with an emphasis on the triad transparency, accountability and social control of public purchases made by the Federal Government through bids and contracts, according to the Access to Information Law, based on the actions of the emergency assistance and humanitarian aid task force and its interconnections with migration and the migratory industry in Roraima. The research contributed to the deepening of the theme in migratory studies, to the production of knowledge about the 'migration industry' in Roraima and to the production of knowledge in the PPGSOF. It aimed to understand the execution of the public budget, through the Social Audit, due to the development of the Venezuelan migration industry in the context of the State of Roraima; apprehend migratory theories in economic perspectives in light of the context of Venezuelan migrations and the participation of migrants and civil society institutions in social control; elucidate the process of the migratory industry and its interconnections with the governance and governance of international and Venezuelan migrations; to develop analyzes of budget execution resulting from governmental actions in the implementation of Operação Acolhida, especially regarding the execution of administrative contracts, under the aspect of law 12.527/11, known as the Law of Access to Information-LAI and rules for handling public resources. Based on the qualitative-quantitative methodology, it concluded that it is unthinkable to deal with migration management, or migration itself, without, however, addressing the industry that involves it, its complexity, and the set of actors that facilitates, sustains and expands the commodification of the process. of international mobility, since migration is big business.